Middle- to late-Holocene storminess in Brittany (NW France): Part II – The chronology of events and climate forcing. (April 2014) - Van Vliet-Lanoë, Brigitte; Penaud, Aurélie; Hénaff, Alain; Delacourt, Christophe; Fernane, Assia; Goslin, Jérôme; Hallégouët, Bernard; Le Cornec, Erwan
This study focuses on the recurring climate conditions required for the largest storms occurring in NW France (Brittany). It is based on the analysed records of storm events along Western Brittany coast (see Part I). In this manuscript (Part II), storm recurrence is explored along with forcing mechanisms. Periods of more frequent storm events over the two last centuries are analysed first in order to link these events with possible forcing mechanisms (North Atlantic Oscillation (NAO) and Atlantic Multidecadal Oscillation (AMO) modes) triggering the most destructive storms. Then, palaeostorm events are discussed at the Holocene scale, from 6000 yr BP to present, to verify the forcing mechanisms. Most recorded events appear to be linked with cooling episodes, mostly in winter, a transition to or from a negative winter NAO mode, a positive AMO mode. Extreme storms occur immediately prior to the 'Medieval Warm Period' (MWP). Maximum effects are reached prior to the onset of the MWP and during the Maunder and Dalton solar minima. Low storm activity occurred during the Spörer Minimum linked to an acceleration of the Atlantic Meridional Overturning Circulation (AMOC). Main storm triggers seem to correspond to a positive AMO mode with an unstable jetstream configuration driving a negative NAO. In this study, four specific weather configurations were defined to explain each type of recorded storminess. The strongest storms correspond to low AMO and decennial-negative NAO modes (e.g. 'Little Ice Age'), or high AMO in association with dominant low NAO modes, as during the early Middle Age and present-day period. Fresh or warm oceans in association with a positive NAO mode are stormy but with very low sting storms frequency. Although in agreement with the orbital forcing and the Holocene glacial history, increasing storm frequency and intensity is most probably partly biased by continuous sea-level rise and resulting erosion.